Based on the Application Practice of Multifunctional Nanomaterials in Art Design and Industrial Manufacturing Concept. (27th August 2022) - Cai, Wensi; Li, Yuze
Abstract : Design is the broad application of discovering new materials and technologies. Nanomaterials have been widely used in product design as a new type of material. The rapid development of nanotechnology is bound to trigger a new design revolution. Combining user needs, design concepts, and material selection, this paper discusses the relationship between user needs and nanoproducts and user needs and nanomaterials. In this paper, the design requirements and related properties of nanomaterials are put forward through the study of the hydration rate of nanomaterials after adding cement, optical microscopy, scanning electron microscopy, and morphology analysis. The effect of the addition of ultrafine materials on the dissolution of ions during cement hydration was studied by ICP technology. The experimental results in this paper show that with the development of the distance, the concentration of calcium ions gradually decreases, and the order of calcium ion concentration is No. 3 tank > No. 4 tank > No. 5 tank. The diffusion of calcium ions was enhanced after the incorporation of nanomaterials, and the diffusion ability of NT to calcium ions was stronger than that of NS group.